ESTIMATION OF LIVING STATURE FROM SELECTED UPPER LIMB ANTHROPOMETRIC MEASUREMENTS: A STUDY ON CENTRAL INDIAN POPULATION (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Stature is considered as one of the important core components. To identify human, besides age, sex and racial affiliation & personal identification of forensic anthropology. The purpose of the study is useful to find out the missing Person’s Identity from fragmented skeletal remains, Amputated Limb or decomposed and dispersed human body parts by Medico-legal experts, forensic examiners and anatomists.Methods: The present study sample was comprised of 670 (302 Males, 368 Females) young and healthy students studying in L.N Medical college and Research center, Bhopal (MP) aged between 17 -25 Years in the period of 2 years. Measurements of stature and three selected parameters of upper limb were taken. Statistical analysis involved by using SPSS Software (version 22.0).Results: Using independent r-test, there was a significant difference (p< 0.001) in the measurement between males and females with regard to Tip of middle finger to 1st crease line of hand, & Tip of middle finger to acromion process of Scapula in both right & left sides, were observed to have strong correlations with stature.Conclusion. The findings of the study show that there was significant positive correlation between the stature and the selected upper limb dimensions and thereby indicating that stature could be predicted successfully to identify skeletal remains among central Indian population.